Pendidikan Remaja (Metode Mawdu'i dalam Perspektif Hadis - Muzakkir Muzakkir (Universitas Islam Negeri Alauddin, 2011)
This topic studies about adolescent development in hadis perspective. The method used in this research is explorative where the writer explored all hadis relating to this topic which have been classified according to the way of hadis research. After analizing some hadis, the writer concludes that adolescent education is very important to bring them reach the maturity. In this case, parents play important role to guide the children to explore their potency through education that is given in the early age